2021
DOI: 10.5758/vsi.200064
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Vascular Resection and Reconstruction in Extremity Soft Tissue Sarcoma and Bone Tumors

Abstract: Purpose This study aimed to evaluate and analyze the feasibility and the oncological and functional outcomes of limb salvage surgery in extremity soft tissue sarcomas (ESTS) and bone tumors invading vessels. Methods Materials and This single-center retrospective analysis included patients with ESTS encasing or invading major blood vessels that were treated by limb salvage surgery with vascular resection and reconstruction between January 1995 and December 2019. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Despite reports of various graft patency rates in previous studies, the results have generally been better in arterial reconstruction than venous reconstruction. 15,16 Shah et al 15 calculated patency according to conduit type in their recent study and found that synthetic grafts seemed to produce poorer patency rates in veins (20%) than in arteries (71.4%). Mlees et al 17 reported a result similar to ours for arterial patency according to conduit and found that arterial graft occlusion rate was not significantly greater in the synthetic graft group than in the autologous vein group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reports of various graft patency rates in previous studies, the results have generally been better in arterial reconstruction than venous reconstruction. 15,16 Shah et al 15 calculated patency according to conduit type in their recent study and found that synthetic grafts seemed to produce poorer patency rates in veins (20%) than in arteries (71.4%). Mlees et al 17 reported a result similar to ours for arterial patency according to conduit and found that arterial graft occlusion rate was not significantly greater in the synthetic graft group than in the autologous vein group.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction options include the use of synthetic or biological grafts. Biological grafts have been reported to have a lower thrombotic rate [ 7 , 16 ]. In our case, the tumor partially encased the popliteal vessels, and we performed en-bloc resection with popliteal vessels and reconstruction with saphenous vein.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-ups were conducted as per protocol [ 7 ], every month for 1 year, every 3 months for the next 2 years, every 6 months for the subsequent 2 years, and annually thereafter. Routine examination was performed using handheld Doppler, and duplex ultrasound (DUS) was performed if the findings were suggestive of graft occlusion.…”
Section: Casementioning
confidence: 99%